BUILDING EFFECTIVE VIRTUAL LEARNING TEAMS THROUGH ENHANCED TEAM PROCESSES - Lu, Hwangji (PEOPLE: International Journal of Social Sciences, 2017)
Information and communication technologies have changed the way how people live, learn and conduct the business activities. The utilization of virtual teams to support cooperative learning becomes a leading topic in distance education. Previous research reveals that the practices of collaborative learning through team interactions enrich students’ learning experiences and prepare them to embrace the real-world problems in the team-based activities. Aligned with the philosophy of learning community, virtual learning teams have reported enhanced student-to-student engagement, raised motivation, higher student satisfaction, greater retention rates, and better academic performance with improved critical thinking, problem-solving, and communication capabilities. In this article, not only challenges are identified, but also strategies to create and facilitate productive virtual learning teams are recommended. These proposed strategies are instrumental in cultivating virtual teams and can be beneficial to instructional designers or instructors who might either integrate the team component into the curriculum or facilitate virtual teams in the online classrooms.